Mortality associated with chronic external radiation exposure in the French combined cohort of nuclear workers. Issue 9 (28th May 2013) - Metz-Flamant, C; Laurent, O; Samson, E; Caër-Lorho, S; Acker, A; Hubert, D; Richardson, D B; Laurier, D
Abstract : Objective: The long-term effects of protracted low level ionising radiation exposure are investigated in a combined analysis of French nuclear workers employed by the Commissariat à l'Energie Atomique (CEA), AREVA Nuclear Cycle (AREVA NC) and Electricité de France (EDF). Associations between cumulative external radiation dose and mortality due to solid cancers, leukaemia and circulatory disease were examined. Methods: All workers hired by CEA, AREVA NC and EDF between 1950 and 1994 who were employed for at least 1 year, badge-monitored for radiation exposure and alive on 1 January 1968 were included. Individual data of annual exposure to penetrating photons (X-rays and gamma rays) were reconstructed for each worker. Estimates of radiation dose–mortality associations were obtained using a linear excess relative risk (ERR) Poisson regression model. Results: Among the 59 021 nuclear workers, 2312 died of solid cancer, 78 of leukaemia and 1468 of circulatory diseases during the 1968–2004 period. Approximately 72% of the cohort had a non-zero cumulative radiation dose estimate, with a mean cumulative dose of 22.5 mSv. Positive but non-significant ERR/Sv were observed for all solid cancers, leukaemia excluding chronic lymphocytic leukaemia (CLL), ischaemic heart diseases and cerebrovascular diseases. A significant ERR/Sv was found for myeloid leukaemia. Conclusions: This is the first combined analysis of major French cohorts of nuclear workers. Results were consistent with risks estimated in other nuclear worker cohorts and illustrate the potential of a further joint international study to yield direct risk estimates in support to radiation protection standards.